Correction: Laws for health and care worker protection and rights: A study of 182 countries. - Matthew M Kavanagh; Adi Radhakrishnan; Vishakh Unnikrishnan; Giorgio Cometto; Catherine Kane; Eric A Friedman; Varsha Srivatsan; Luis Gil Abinader; James Campbell; Health & Care Worker Policy Lab (PLOS Global Public Health)
[This corrects the article DOI: 10.1371/journal.pgph.0003767.].